Purification and characterization of the prohormone convertase PC1(PC3). - Yi Zhou; Iris Lindberg (1993)
The prohormone convertases PC1 (also known as PC3) and PC2 have been implicated in the biosynthesis of several polypeptide hormones and neuropeptides. In order to understand the regulation and the cell biology of prohormone cleavage, we have purified recombinant mouse PC1 from the conditioned medium of overexpressing Chinese hamster ovary cells. Recombinant PC1 was found to be an 87-kDa calcium-dependent proteinase with an inhibitor profile similar to that of Kex2 and furin. However, unlike furin, the optimum pH for PC1 activity is between pH 5.5 and 6.5. Like furin, the enzyme is activated at millimolar rather than at micromolar concentrations of calcium. Chinese hamster ovary/PC1 cells secrete the mature form of PC1, converted by a proteolytic cleavage on the carboxyl side of the RSKR motif located at residues 80-83. This conversion occurs very early in biosynthesis, suggesting that, like Kex2 and furin, PC1 may be activated autocatalytically. Specificity studies with fluorogenic substrates showed that the enzyme prefers substrates with an arginine 4 amino acids amino-terminal to the cleavage site; synthetic tripeptide substrates containing only pairs of basic amino acids are not well cleaved. However, the neuropeptide precursor proenkephalin is cleaved by PC1 to yield a peptide B-sized peptide; since peptide B represents the naturally occurring carboxyl-terminal fragment of proenkephalin, these data suggest a role for PC1 in the processing of this precursor.